PENGARUH STRES KERJA, LINGKU.NGAN .KERJA FISIK DAN KOMPENSASI FINANSIAL. TERHADAP KINERJA KARYAWAN - Tresna Wijaya, Made Yogi; Sudibya, Gede Adnyana (E-Jurnal Manajemen; Vol 3 No 11 (2014), 2014)
ABSTRACT Performance is work result that shown by employee or real behavior that shown as their roles in organization. Puri Raja Kuta Badung Hotel becomes the research location with 90 employees as respondent. Data analysis technique that was used to test hypothesis is couple linear regression analysis that has aim to know simultaneously and partially effect and also to determine dominant variable that affect employee’s performance. Based on analysis result known that work stress variable, physical work environment and financial compensation has significant effect simultaneously to employee’s performance in Puri Raja Kuta Badung Hotel by 84,7 percent contribution. Work stress variable, physical work environment and financial compensation also has significant effect partially to employee’s performance at Puri Raja by compensation variable that has greatest effect to employee’s performance. Puri Raja Hotel is expected to notice works stress, physical work environment and financial compensation so it can increase employee’s performance so it can reach the goal that set by the company.
Keywords: employee’s performance, work stress, physical work environment and financial compensation